Viscosity of aqueous carbohydrate solutions at different temperatures and concentrations - Telis, V. R. N.; Telis-Romero, J.; Mazzotti, H. B.; Gabas, A. L. (Taylor & Francis Inc, 2007)
Experimental viscosity values of sucrose, glucose, and fructose aqueous solutions in a large range of temperatures (0 to 85 degrees C) and concentrations (10 to 60% w/w) that might be encountered in food processes were obtained in order to contribute to extending the available database of food properties. The temperature dependence of viscosity could be adequately described by the Arrhenius model, and the activation energy was well represented by a unique function of the solute volume fraction, valid for sucrose, glucose, and fructose solutions.
Keywords: sucrose; glucose; fructose; sugar solutions; Arrhenius model